Isoprenaline and salbutamol inhibit pyroptosis and promote mitochondrial biogenesis in arthritic chondrocytes by downregulating β-arrestin and GRK2 - Ajmal, Iqra; Farooq, Muhammad Asad; Abbas, Syed Qamar; Shah, Jaffer; Majid, Muhammad; Jiang, Wenzheng (Frontiers in Pharmacology, 2022)
Rheumatoid arthritis and osteoarthritis overlap many molecular mechanisms of cartilage destruction. Wear and tear in cartilage is chondrocyte-mediated, where chondrocytes act both as effector and target cells. In current study, role of β2-AR was studied in chondrocytes both in vitro and in vivo. High grade inflammation in vitro and in vivo disease models led to decline in anti-inflammatory β2-AR signaling and use of β2-AR agonist attenuated arthritis symptoms. Detailed analysis in chondrocytes revealed that Isoprenaline (ISO) and Salbutamol (SBT) increased cell viability and relative Bcl-2 expression, meanwhile, decreased proteins levels of TNF-α, IL-6 and IL-8 in arthritic chondrocytes when compared with control, respectively. SBT preserved physiological concentration of antioxidant enzymes (CAT, POD, SOD and GSH) in cartilage homogenates and ISO inhibited IL-1β-mediated genotoxicity in arthritic chondrocytes. Moreover, β2-AR agonist increased mitochondrial biogenesis and proteoglycan biosynthesis by upregulating the gene expression of PGC1-α, NRF2 and COL2A1, Acan, respectively. ISO and SBT inhibited extracellular matrix (ECM) degradation by downregulating the gene expression of MMP1, MMP3, MMP9 and ADAMTS5 in vitro and in vivo study. In mechanism, β2-AR agonists decreased β-arrestin and GRK2 pathway, and as a result mice receiving SBT did not exhibit severe disease. Hence our data suggest β2-AR agonist administered at disease onset can inhibit receptor internalization by downregulating the expression of β-arrestin and GRK2 in chondrocytes.